Bone defect management with tissue-engineered constructs based on deproteinized cancellous bone: an experimental study - Evgeniya A. Anastasieva; Liliya A. Cherdantseva; Tatyana G. Tolstikova; Irina A. Kirilova (Гений oртопедии, 2023)
Background Management of bone defects with autologous bone grafting has always been the "gold standard" but it is not always possible to use it for a number of reasons. Preprocessed materials of biological and non-biological origin were developed as an alternative. A new branch of these materials is tissue-engineered constructs that fully imitate autologous bone in required volume. Aim is to study in vivo the possibility of using deproteinized human cancellous bone tissue as a matrix for creating tissue-engineered constructs. Methods The study was carried out on 24 NZW line rabbits, since this line has a fully characterized stromal-vascular fraction formula (SVF). The study design included 3 groups. Fiкst group (control) had surgical modeling of bone defects in the diaphysis of the contralateral femur without reconstruction; Group 2 had bone defect reconstruction using fragments of a deproteinized cancellous bone graft; group 3 underwent bone defect reconstruction using fragments of deproteinized cancellous bone matrix along with the autologous adipose tissue SVF (obtained according to ACP SVF technology). Animals were sacrificed with ether anesthesia at 2, 4 and 6 weeks after the operation and subsequent histological study followed. Result During all periods of the study, the newly formed bone tissue volume density in the 3rd group (reconstruction with deproteinized human cancellous bone + stromal-vascular fraction) was 1.78 times higher (p < 0.001) than in the first group (bone defect without reconstruction), 1.21 times higher (p < 0.001) than in the 2nd group (reconstruction with deproteinized cancellous bone alone). The dynamics of changes in the mature bone tissue volume density was similar to those of the newly formed bone tissue. Discussion The comparative analysis of reparative processes using a tissue engeneered construst based on deproteinized cancellous human bone with adipose tissue stromal vascular fraction revealed that the use of these bone substitute materials contributes not only to the early activation of reparative regeneration of the main structural elements of bone tissue at the site of bone defect, but also their timely differentiation. Conclusion The use of deproteinized cancellous bone matrix combined with stromal-vascular fraction to create a tissue-engineered construct could unleash several regeneration mechanisms and accelerate the process of bone defect site repair, compared with 1st and 2nd group of study.